2018
DOI: 10.1103/physrevlett.121.115501
|View full text |Cite
|
Sign up to set email alerts
|

Two Diverging Length Scales in the Structure of Jammed Packings

Abstract: At densities higher than the jamming transition for athermal, frictionless repulsive spheres we find two distinct length scales, both of which diverge as a power law as the transition is approached. The first, ξ_{Z}, is associated with the two-point correlation function for the number of contacts on two particles as a function of the particle separation. The second, ξ_{f}, is associated with contact-number fluctuations in subsystems of different sizes. On scales below ξ_{f}, the fluctuations are highly suppres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 45 publications
7
49
0
Order By: Relevance
“…Finding differences between 2d and 3d, we also consider 4d and mean-field variants of the jamming model. These appear to be consistent with results from 3d, suggesting that the the upper critical dimension is below three [7].To summarize, in this paper (i) we introduce an entirely new procedure (in the context of jamming) for finite size scaling analysis, by comparing subsystems of a large packing with periodic packings of the same size; (ii) we identify a new length scale, in addition to the ones reported in [6]; (iii) we provide accurate measurements of this new length scale in dimension d = 2, 3, 4 (note that previous calculations of jamming length scales could only obtain accurate results for 2d systems); (iv) thanks to this improved finite size scaling analysis, we obtain strong quantitative evidence that d u ∼ 2 is the upper critical dimension; (v) we analyze models with hypostatic jamming and find that the corresponding suppression of fluctuations does not take place. Our analysis thus shows that anomalous contact fluctuations survive in mean-field like models, and are crucially related to isostaticity.We begin by defining the jamming model, in which overlapping particles of radius R i interact via a harmonic potential:Here, r ij is the distance between the centers of the particles and the Heaviside step function, Θ (x), insures that only overlapping particles interact.…”
supporting
confidence: 80%
See 4 more Smart Citations
“…Finding differences between 2d and 3d, we also consider 4d and mean-field variants of the jamming model. These appear to be consistent with results from 3d, suggesting that the the upper critical dimension is below three [7].To summarize, in this paper (i) we introduce an entirely new procedure (in the context of jamming) for finite size scaling analysis, by comparing subsystems of a large packing with periodic packings of the same size; (ii) we identify a new length scale, in addition to the ones reported in [6]; (iii) we provide accurate measurements of this new length scale in dimension d = 2, 3, 4 (note that previous calculations of jamming length scales could only obtain accurate results for 2d systems); (iv) thanks to this improved finite size scaling analysis, we obtain strong quantitative evidence that d u ∼ 2 is the upper critical dimension; (v) we analyze models with hypostatic jamming and find that the corresponding suppression of fluctuations does not take place. Our analysis thus shows that anomalous contact fluctuations survive in mean-field like models, and are crucially related to isostaticity.We begin by defining the jamming model, in which overlapping particles of radius R i interact via a harmonic potential:Here, r ij is the distance between the centers of the particles and the Heaviside step function, Θ (x), insures that only overlapping particles interact.…”
supporting
confidence: 80%
“…1). Recently it has been found that the contact statistics possess unusual long range correlations near the transition [6]. We therefore focus on contact fluctuations to compare the two ensembles.While we expect convergence of the two ensembles for large enough systems, the system size V * for which these converge appears to be in many cases well beyond that accessible via simulations.…”
mentioning
confidence: 99%
See 3 more Smart Citations